Screening for Wilson’s disease in acute liver failure: A new scoring system in children - Feng, Cai-Xia; Chen, Xiu-Qi; He, Xiao-Li; Lan, Lian-Cheng; Tang, Qing; Huang, Li; Shan, Qing-Wen (Frontiers in Pediatrics, 2022)
Background: Wilson’s disease (WD) is a rare cause of acute liver failure (ALF) and has a high fatality rate. Rapid and accurate diagnosis is important for ALF because of WD (ALF-WD). Our objective was to establish a simple, rapid, and accurate diagnostic test to distinguish ALF-WD from non-WD ALF (NWDALF) in children. Methods: The data from all cases with pediatric ALF were retrospectively collected and analyzed. We performed receiver operator characteristics curve (ROC) analysis and confirmed the optimum cut-off points. Results: Fifty-eight patients with pediatric ALF (12 with WD, 46 with other etiologies) were included. Older age was observed in ALF-WD compared to NWDALF (11.16 ± 2.51 years vs. 3.34 ± 3.81 years, p < 0.001). An analysis based on routine biochemical testings revealed that total bilirubin (TBil), direct bilirubin, indirect bilirubin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), AST:ALT ratio, alkaline phosphatase (ALP), ALP:TBil ratio, serum albumin, gamma-glutamyl transferase, cholinesterase, hemoglobin, and platelet were statistically significant between the ALF-WD and NWDALF groups. The optimum cut-off points were obtained through ROC analysis. A scoring system was formed by assigning a score of 1 or 0 to patients who met the 13 cut-off points. Using ROC analysis, we determined a cut-off point of ≥6.5 for ALF-WD with 91.7% sensitivity and 97.8% specificity (p <0.0001). In addition, a best cut-off point of ≥1.5 based on only five variables (ALT, AST, AST:ALT ratio, ALP, and ALP:TBil ratio), had 100% sensitivity and 91.3% specificity for ALF-WD (p <0.0001). Based on this, when age was calculated as the sixth indicator, the best cut-off value of ≥2.5 had 100% sensitivity and 97.8% specificity (p <0 .0001). Conclusions: Our study developed a new scoring system that consists of simple laboratory tests with good sensitivity and specificity and can be used by clinicians to quickly distinguish ALF-WD from NWDALF in children.